Cloacal Malformation with Associated Urethral Atresia - Al-Shamai; Tiusaba Tiusaba; Jacobs Jacobs; Russell Russell; Bokova Bokova; Pohl Pohl; Varda Varda; Ho Ho; Feng Feng; Badillo Badillo; Levitt Levitt (Georg Thieme Verlag KG, 2023)
Introduction Cloacal malformations comprise a heterogeneous group of anomalies that are considered the most complex anorectal malformations (ARMs) in females. Precise evaluation to identify the unique anatomy prior to reconstruction with collaboration between colorectal surgeons, urologists, and gynecologists is vital. Here, we present a rare anatomical variation in a patient with a cloacal malformation which affected operative and postoperative management.